Brahma-related gene 1 acts as a profibrotic mediator and targeting it by micheliolide ameliorates peritoneal fibrosis - Shuting Li; Congwei Luo; Sijia Chen; Yiyi Zhuang; Yue Ji; Yiqun Zeng; Yao Zeng; Xiaoyang He; Jing Xiao; Huizhen Wang; Xiaowen Chen; Haibo Long; et al. (Journal of Translational Medicine, 2023)
Abstract Background Progressive peritoneal fibrosis is a worldwide public health concern impacting patients undergoing peritoneal dialysis (PD), yet there is no effective treatment. Our previous study revealed that a novel compound, micheliolide (MCL) inhibited peritoneal fibrosis in mice. However, its mechanism remains unclear. Brahma-related gene 1 (BRG1) is a key contributor to organ fibrosis, but its potential function in PD-related peritoneal fibrosis and the relationship between MCL and BRG1 remain unknown. Methods The effects of MCL on BRG1-induced fibrotic responses and TGF-β1-Smads pathway were examined in a mouse PD model and in vitro peritoneal mesothelial cells. To investigate the targeting mechanism of MCL on BRG1, coimmunoprecipitation, MCL-biotin pulldown, molecular docking and cellular thermal shift assay were performed. Results BRG1 was markedly elevated in a mouse PD model and in peritoneal mesothelial cells cultured in TGF-β1 or PD fluid condition. BRG1 overexpression in vitro augmented fibrotic responses and promoted TGF-β1-increased-phosphorylation of Smad2 and Smad3. Meanwhile, knockdown of BRG1 diminished TGF-β1-induced fibrotic responses and blocked TGF-β1-Smad2/3 pathway. MCL ameliorated BRG1 overexpression-induced peritoneal fibrosis and impeded TGF-β1-Smad2/3 signaling pathway both in a mouse PD model and in vitro. Mechanically, MCL impeded BRG1 from recognizing and attaching to histone H3 lysine 14 acetylation by binding to the asparagine (N1540) of BRG1, in thus restraining fibrotic responses and TGF-β1-Smad2/3 signaling pathway. After the mutation of N1540 to alanine (N1540A), MCL was unable to bind to BRG1 and thus, unsuccessful in suppressing BRG1-induced fibrotic responses and TGF-β1-Smad2/3 signaling pathway. Conclusion Our research indicates that BRG1 may be a crucial mediator in peritoneal fibrosis and MCL targeting N1540 residue of BRG1 may be a novel therapeutic strategy to combat PD-related peritoneal fibrosis.